Seoul’s Paradiplomacy To The Global Public: The Involvement of Bangtan Sonyeondan (BTS) in the Tourism Industry - Gilang Nur Alam; RMT Nurhasan Affandi; Windy Dermawan; Fuad Azmi; Emil Mahyudin (Journal of Governance, 2022)
This study aims to analyze the use of the Bangtan Sonyeondan (BTS) as an instrument of the paradiplomacy of Seoul, South Korea, in promoting the city’s tourism to the global public on economic and cultural aspects. Seoul's paradiplomacy in promoting tourism is motivated by efforts to attract global public attention and to encourage foreign tourists to make Seoul a tourist destination. For that purpose, the Seoul Metropolitan Government has collaborated with various K-pop artists, such as BTS, in its paradiplomacy practice. This study uses transgovernmentalism, foreign relations, paradiplomacy, and art as theories and qualitative research as a method by taking data directly and indirectly. Direct data are obtained from interviews with several informants, while indirect data are obtained from studies of relevant documentation and literature. This study finds that BTS becomes an instrument of Seoul's paradiplomacy in tourism promotion. The researchers also discovered that the Seoul Metropolitan Government has restructured the Seoul Tourism Organization from a public-private partnership and government-invested institution to one that can increase the city's competitiveness in tourism and Meetings, Incentive Tours, Conventions, and Exhibitions (MICE), as well as contribute to Seoul's economic development by revitalizing tourism-related industries.